The Influence of Cyberloafing on Workplace Outcomes: A Study Utilizing the Job Demands-Resources (JD-R) Theory - Adacha Felix Kwala; Mary Agoyi (SAGE Open)
The integration of the Internet into business operations has led to the rise of cyberloafing, which involves engaging in non-work-related online activities during work hours. This study adopts a novel approach using Job Demands-Resources (JD-R) theory to explore the positive aspects of cyberloafing and its impact on employee well-being. Conducted with a sample of 255 employees from diverse sectors in the Turkish Republic of Northern Cyprus (TRNC), this study investigated how cyberloafing can reduce perceived stress, provide mental breaks, and foster creativity and innovation. Challenging traditional views that consider cyberloafing as purely counterproductive, this study posits that it can be a potential resource for enhancing well-being. Utilizing partial least squares structural equation modeling (PLS-SEM) via SmartPLS 4, the analysis revealed significant relationships between cyberloafing, stress reduction, mental relaxation, and creativity, which collectively contributed to improved employee performance and well-being. The findings suggest that under the right conditions, cyberloafing serves as an effective coping mechanism that promotes both innovation and stress relief. This study offers valuable insights for organizations by highlighting strategies to leverage the positive aspects of cyberloafing while managing its risks.